Unorthodox training - Morales, T. (Swimming Technique, 2004)
In an attempt to revolutionize swimming, Gary Hall Jr. formed The Race Club not only to prepare swimmers for the Olympic Games in Athens, but to create bigger and better opportunities for the next generation. The concept of the club is described in the article.